2019
DOI: 10.1186/s40360-019-0374-y
|View full text |Cite
|
Sign up to set email alerts
|

KEA-1010, a ketamine ester analogue, retains analgesic and sedative potency but is devoid of Psychomimetic effects

Abstract: BackgroundKetamine, a widely used anaesthetic and analgesic agent, is known to improve the analgesic efficacy of opioids and to attenuate central sensitisation and opioid-induced hyperalgesia. Clinical use is, however, curtailed by unwanted psychomimetic effects thought to be mediated by N-methyl-D-aspartate (NMDA) receptor antagonism. KEA-1010, a ketamine ester-analogue designed for rapid offset of hypnosis through hydrolysis mediated break-down, has been shown to result in short duration sedation yet prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…We conclude that ketamine-induced dissociation and analgesia are independent, suggesting that ketamine can be refined into a more targeted pain therapeutic. 8,11 We also conclude that ketamine may be used as a probe to advance our knowledge of dissociation independent pain circuits. We found that…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We conclude that ketamine-induced dissociation and analgesia are independent, suggesting that ketamine can be refined into a more targeted pain therapeutic. 8,11 We also conclude that ketamine may be used as a probe to advance our knowledge of dissociation independent pain circuits. We found that…”
Section: Discussionmentioning
confidence: 78%
“…We conclude that ketamine-induced dissociation and analgesia are independent, suggesting that ketamine can be refined into a more targeted pain therapeutic. 8,11 We also conclude that ketamine may be used as a probe to advance our knowledge of dissociation independent pain circuits. We found that dissociation did not entirely mediate the relation of analgesics to pain reduction although it may partly do so, and further replication of these effects would be desirable.…”
Section: Discussionmentioning
confidence: 81%
“…Independent from whether psychedelics will be approved as medicines, the knowledge generated is creating a unique opportunity for the development of novel, more efficacious designer drugs with structural analogy to psychedelic compounds (McLean et al, 2006;Zanos et al, 2017;Kenakin, 2019). Such a paradigm is already being explored for the design of a ketamine-and opioid-like analgesic with reduced side effects and could be employed in designing antidepressant and anxiolytic molecules with enhanced efficacy and reduced side effects (Manglik et al, 2016;Conibear and Kelly, 2019;Harvey et al, 2019). If skillfully harnessed, the knowledge generated could drastically improve our pharmacotherapeutic toolbox in psychiatry.…”
Section: Psychedelic-induced Biased Phosphoproteomicsmentioning
confidence: 99%
“…Ultimately, the knowledge generated by ongoing clinical studies may boost the acceptance of this approach by legislative, funding, and academic bodies, leading to the implementation of the necessary policy shifts to allow this therapy to reach the bedside. Lastly, compounds with structural analogy might represent an alternative to natural and semisynthetic psychedelics in an attempt to decouple the therapeutic from psychedelic effects of these compounds (McLean et al, 2006;Zanos et al, 2017;Harvey et al, 2019;Kenakin, 2019). For example, 2-([2-(4-cyano-2,5-dimethoxyphenyl)ethylamino]methyl)phenol, a novel and synthesized derivate of N-benzyl-substituted phenethylamine hallucinogens, displays strong binding affinity and selectivity for the 5HT 2A receptor (Hansen et al, 2014;Jensen et al, 2020).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Based on the R5 brain slice findings, we hypothesized that BaCl 2 would antagonize a central analgesic effect of R5. Rats were used for this investigation because previous behavioral investigations had utilized the rat model ( 5 , 6 , 8 , 26 ). The reason for this is the necessity for secure intravenous tail vein access for drug delivery, which limits drug metabolism by tissue esterases ( 27 ).…”
Section: Intraventricular Microinjection Of R5 and Effect Of Barium C...mentioning
confidence: 99%